2022
DOI: 10.3390/jcm11092511
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of S2-Alar-Iliac Screw Trajectories between Males and Females Using Three-Dimensional Computed Tomography Analysis: The True Lateral Angulation of the S2-Alar-Iliac Screw in the Axial Plane

Abstract: The S2 alar-iliac screw (S2AIS) is commonly used for long spinal fusion as a rigid distal foundation in spinal deformity surgeries, and it is also used in percutaneous sacropelvic fixation for providing an in-line connection to the proximal spinal constructs without using offset connectors. Although the pelvic shape is different between males and females, reports on S2AIS trajectories according to gender have been scarce in the literature. In this paper, S2AIS trajectories are compared between males and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These results are consistent with those of previous studies. In Funao et al’s report 24) using 3D CT analysis, the maximum length and minimal intraosseous area on the perpendicular plane of the S2AIS pathway were significantly longer and larger in men and women. Wang et al 25) also indicated that the modified sacroiliac screws, measured on the 3D pelvis model, were thicker and longer in men than in women, suggesting that it would stem from the anatomical differences between the sexes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These results are consistent with those of previous studies. In Funao et al’s report 24) using 3D CT analysis, the maximum length and minimal intraosseous area on the perpendicular plane of the S2AIS pathway were significantly longer and larger in men and women. Wang et al 25) also indicated that the modified sacroiliac screws, measured on the 3D pelvis model, were thicker and longer in men than in women, suggesting that it would stem from the anatomical differences between the sexes.…”
Section: Discussionmentioning
confidence: 88%
“…Zhu et al 23) reported that the trajectory of S2AIS in women was 5° more caudal than that in men in the Asian population. Funao et al 24) also documented that the insertion angle of S2AIS was significantly different between men and women. Thus, we suggest that the anatomical differences between the sexes should be considered when determining the screw size and insertion angle pre- and intraoperatively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to new technology outside of the operating room, advancements in intraoperative techniques have been utilized to improve the success rates of spinal deformity surgery. In a study conducted by Funao et al, sacropelvic fixation with S2-alar-iliac screws (S2AI) based on patient sex was evaluated in adults, given the innate difference in pelvic size and shape between males and females [ 9 ]. Three-dimensional pelvic computed tomography was used to determine ideal trajectory pathways for S2AI screw placement, which was determined to be more laterally angled in the axial plane in females (right 47.7°, left 46.1°) than in males (right 45.3°, left 44.3°), and more horizontally angled in the coronal plane in females (right 33.7°, left 34.5°) than in males (right 36.5°, left 37.0°).…”
mentioning
confidence: 99%